Effects of brain-breaks exercise video program on fundamental motor skills performance among the primary school students in Kapit, Sarawak - John, Jeswenny Fresshila Anak (2023)
Proficiency in Fundamental Motor Skills (FMS) among children is important for children to engage in physical activity (PA) and live an active lifestyle which will bring positive implications to their physical, cognitive, and social development. However, there is evidence that indicates low proficiency in FMS among children. The study involved two interrelated studies and was divided into 2 phases: (1) Crosssectional study (2) Interventional study. Data for both study phases were collected using the Canadian Agility and Movement Skill Assessment (CAMSA) instrument. Phase 1 of the study aimed to identify the Sarawakian children’s FMS test scores based on gender and to identify the percentiles of total FMS score among Sarawakian children based on gender and age. Data were analysed using the descriptive statistics (mean, standard deviation, percentiles, crosstabs). 385 students were randomly selected from 4 invited primary schools from 3 divisions in Sarawak (Kuching, Kota Samarahan, Kapit). Males scored higher than females in all variables; completion time (males, 28.65 ± 6.29; females, 28.09 ± 5.15), time score (males, 3.04 ± 2.20; females, 2.93 ± 1.82), skill score (males, 8.39 ± 2.51; females, 7.84 ± 2.62), total CAMSA score (males, 11.42 ± 3.91; females, 10.77 ± 3.62), and interpretation (males, 1.09 ± .30; females, 1.06 ± .23). In addition, the the Sarawakian children’s total FMS score percentiles were lower as compared to the Canadian children. Phase 2 aimed to examine the effects of Brain-Breaks exercise video program in FMS performance among the primary school students in Kapit, Sarawak. 104 students from 2 invited primary schools in Kapit, Sarawak participated in the study. Following the pre-test, the schools were randomly assigned to an intervention group (n = 53) and a control group (n = 51). The intervention group received two-30 minutes Brain-Breaks sessions per week for 7 weeks and the control group continued with their regular Physical Education (PE) class for 7 weeks. A post-test was conducted following the 7-week intervention. Mixed factorial analysis of variance (ANOVA) was used to examine the effects of Brain-Breaks on the study variables. A mixed ANOVA showed significant changes (time effect) on skill score, F(1,102) = 73.85, p-value = < .001; total CAMSA score, F(1, 102) = 52.94, p-value = < .001; and interpretation, F(1, 102) = 15.57, pvalue = < .001. There were also significant differences between groups on skill score, F(1, 102) = 35.21, p-value = < .001; and total CAMSA score, F(1, 102) = 5.81, pvalue = .018. A significant interaction effect was found for skill score, F(1, 102) = 17.07, p-value = < .001. In conclusion, the skill score and total CAMSA score among primary school students significantly improved following the Brain-Breaks intervention. Behavioural change intervention programs and strategies are essential in the acquiring of fundamental motor skills among the primary school students which are central to sports participation and physical activities.